PENGARUH PARTISIPASI DALAM PENYUSUNAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH KABUPATEN BATANG HARI - Etty Siswati (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
The purpose of this study is (1) To determine the effect of participation in the budgetary performance of Local Government Officers Batang Hari, the data collection method used survey method was used to obtain information from respondents by using interview techniques and disseminate a list of questions and using the measurement scale Likert. The population in this study is covering the whole head of SKPD, Number 52 stratified random sampling data with the allocation of two respondents each stratum, in this case on education as strata. Data analysis tool used is multiple regression method using computer assistance through the program SPSS 20.0 for windows.The results of the analysis show participation, positive and significant effect on the performance of local government officials. Keywords: Participation, Performance and Local Government Officials Batang Hari